PHYSICAL CULTURE IN SCHOOL-AGE CHILDREN - Jabbarov Umid Soltiboldiyevich (Journals Park Publishing, 2022)
This article provides the necessary information about the development of physical culture of school-aged students in physical education classes, and this thesis is recommended for use as a methodical guide for secondary school teachers.
Keywords: Physical culture, tasks, childhood, sports, development, defense of the homeland, education, lifestyle, healthy life, features.